Antimicrobial resistance of three common molecularly identified pathogenic bacteria to Allium aqueous extracts. (May 2020) - Serrano, Héctor D. Arzate; Mariezcurrena-Berasain, María A.; Del Carmen Gutiérrez Castillo, Adriana; Carranza, Benjamín Valladares; Pliego, Alberto Barbabosa; Rojas, Martín Talavera; Anele, Uchenna Y.; Salem, Abdelfattah Z.M.; Rivas-Caceres, Raymundo R.
Abstract: The aim of this work was to evaluate the in vitro bacterial inhibition of different types of garlic on Escherichia coli ATCC 25922, Listeria monocytogenes and Staphylococcus aureus . The bacterial strains were molecularly identified using gen 16S rDNA molecular identification. Four different types of garlics were used: 1) white, 2) Japanese, 3) elephant and 3) black, and these were evaluated at two different concentrations (0.25 and 0.125 g/mL) per garlic type. Bioactive compounds present in the garlics were identified using high-performance liquid chromatography coupled to ultraviolet detector (HPLC-UV), and total polyphenols were quantified by the Folin-Ciocalteu technique. The Kirby-Bauber method was used for the bacterial evaluation. Aqueous extract of black garlic had the highest amount of polyphenols 6.26 ± 0.21 mg GAE/mL. The area of inhibition was measured and classified as sensitive, intermediate or resistant. Using the disc diffusion assay, higher concentration (0.25 g/mL) of aqueous extract of white garlic had the highest antibacterial activity area, with 21.46 ± 3.94 mm for L. monocytogenes, 20.61 ± 2.47 mm for S. aureus and 17.83 ± 2.21 mm for E. coli. White garlic had comparable antimicrobial activity as the control (tetracycline at 30 μg) as indicated by the size of the inhibition halos. Based on your results, white garlic can be used as an alternative to synthetic antimicrobials. Highlights: Antibacterial activity of Allium sp. extracts was assayed. Aqueous extract of white garlic had the best antibacterial activity at 0.25 g/mL. Black garlic extract had no antimicrobial action on the pathogenic bacteria. Extracts can be used as alternatives to replace synthetic antimicrobials.